COVID-19 in an asymptomatic patient undergoing FDG PET/CT (2020)
The 2019 novel coronavirus pneumonia (COVID-19) is an ongoing global pandemic with a worldwide death toll of over 416,000 as of June 10, 2020. Although the first documented cases in Wuhan, China were patients with severe respiratory symptoms including cough,fever,fatigue, and shortness of breath, the disease process can also be asymptomatic. In this case report, an asymptomatic 63-year-old male with Lynch syndrome undergoing a routine staging fluorodeoxyglucose positron-emission tomography/computed tomography was found to have typical radiologic features of COVID-19 with marked pulmonary FDG uptake and was subsequently diagnosed via reverse-transcription polymerase chain reaction. Many studies have described the appearance of COVID-19 on chest radiography and CT with the most common imaging features being bilateral, peripheral, and basilar predominant ground glass opacities and consolidation. Although these findings are typically nonspecific for an atypical lung infection, early recognition of COVID-19 in the setting of a global pandemic (even in the asymptomatic patient) is critical in order to limit the spread of disease.